Economic Impact on the Re-opened Scalloping Area for Citrus County, Florida—2003 - Tom Stevens; Charles Adams; Alan Hodges; David Mulkey (EDIS)
This is EDIS document FE493, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published August 2004.